(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2022)
A cranial contour defect can occur when bone is removed following direct trauma, removal of a tumor or for surgical access to the brain. These defects impair function (protection) and aesthetic contour and require a design strategy for reconstructing the defect. In principle, if the defect is unilateral (one side) then designing a form to restore the contour could be assisted by attaining a mirror image of the undamaged side of the skull. As an alternative to mirroring the undamaged skull an interpolated surface could also be generated for repairing this cranial defect. A case with a unilateral left temporal bone defect was considered for this study. A cranioplasty reconstruction was to be performed to restore the bone contour. The patient’s Computed Tomography (CT) scan (1 mm slice thickness) was saved in the raw file format Digital Imaging and Communication in Medicine (DICOM). The DICOM data was converted to a standard tesselation file (stl.) using MIMICS software (Materialise V24. Belgium). The stl. file of the skull was used to generate a 3D design of the implant using Computer-aided Design/ Computer-aided Manufacturing (CAD/CAM) software. The design was used to 3D print a base template, which could finally be used to fabricate the physical implant to restore the defect. This case explored the two techniques of mirroring and interpolation for repairing a cranial defect. A comparison of the two techniques was performed. Feedback from the surgeon suggested that interpolation provided a digitally accurate implant surface comparable to a mirrored one.